Multiple sclerosis and obesity: The role of adipokines - Correale, Jorge; Marrodan, Mariano (Frontiers in Immunology, 2022)
Multiple Sclerosis (MS) is a chronic inflammatory disease of the central nervous system (CNS) leading to demyelination, and neurodegeneration. Although its pathogenesis is not yet fully understood, there is considerable evidence to suggest MS arises from complex interactions between individual genetic susceptibility and external environmental factors. In recent decades, population-based studies have provided evidence indicating the prevalence of MS is increasing worldwide, in parallel with the rise in obesity and metabolic syndrome. This synchronous increment in the incidence of both MS and obesity has led to a search for potential biological mechanisms linking both conditions. Notably, a large number of studies have established significant correlation between obesity and higher prevalence, or worse prognosis, of several immune-mediated conditions. Fat tissue has been found to produce a variety of soluble factors named adipokines. These mediators, secreted by both adipocytes as well as diverse immune cells, participate in a wide range of biological functions, further strengthening the concept of a link between immune function, metabolism, and nutritional state. Because obesity causes overproduction of pro-inflammatory adipokines (namely leptin, resistin and visfatin) and reduction of anti-inflammatory adipokines (adiponectin and apelin), adipose tissue dysregulation would appear to contribute to a state of chronic, low-grade inflammation favoring the development of disease. In this review, we present a summary of current knowledge related to the pathological effects of different adipokines, prevalent in obese MS patients.